Young and old users prefer immersive virtual reality over a social robot for short-term cognitive training. Issue 161 (May 2022) - Cohavi, Orit; Levy-Tzedek, Shelly
Highlights: Spatial/social presence used to gamify cognitive training for young and old adults. Immersive-VR training (spatial) preferred over training with a robot (social). Preferences for VR-training over robot-training did not correlate with age or gender. Results contrast with previous works on the value of physical embodiment. Abstract: Socially Assistive Robots (SARs) and immersive Virtual Reality (iVR) are interactive platforms that promote user engagement, which can motivate users to adhere to therapeutic frameworks. SARs use social presence to create affective relationships with users, leveraging the human tendency to be driven by social interactions. iVR uses spatial presence to provide an intense multisensory experience that submerges users in a virtual world. We adapted two such platforms – a SAR and an iVR – to deliver cognitive training (CT), by integrating established cognitive tasks in gamified environments that convey a strong sense of presence. Sixty-four participants underwent CT with both platforms. We tested: (1) their perception of both platforms; (2) whether they preferred one over the other in the short term; (3) their projected preferences for long-term training; and (4) whether their preferences correlated with personal characteristics. They preferred the virtual experience in the short term across age and gender. For long-term CT, there was equal projected preference for both platforms. It may be that a combination of social and spatial presence might yield engagement in long-term training.